THE ROLES OF TEACHERS AND STUDENTS IN CLASSROOM - Norova , Zarina Zohidjon qizi; Amonova, Feruza Baxtiyor qizi; Burkhanova , Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
Teaching can be either teacher-centered or student-centered or a combination of both. Teacher -centered teaching has been in practice for centuries. Learner-centered instruction, on the other hand is quite a recent approach growing. Now it seems to have won ground over traditional teacher-centered instruction in many educational institutions and among educationists ‘ circles in many parts of the world.